Study on Acute Toxicity of Amiodarone New Complexes With Cyclodextrin - Ghiciuc, Cristina Mihaela; Shleghm, Maytham Razaq; Vasile, Cornelia; Tantaru, Gladiola; Creteanu, Andreea; Ochiuz, Lacramioara (Frontiers in Pharmacology, 2021)
Amiodarone low solubility and high permeability is the limiting step for its bioavailability, therefore new formulations are needed to increase its oral bioavailability Complexation of Amiodarone with Cyclodextrin results in improved dissolution rate, solubility and bioavailability and allows for a more controlled drug release. We characterized the acute toxicity of a new Amiodarone cyclodextrin complex, administered orally in laboratory animals.